Clinical features, risk factors, and prognosis of anthracycline-induced cardiotoxicity in patients with malignant lymphoma who received a CHOP like regimen. (25th November 2020) - Nakayama, T; Oshima, Y; Kusumoto, S; Osaga, S; Yamamoto, J; Wakami, K; Goto, T; Sugiura, T; Seo, Y; Iida, S; Ohte, N
Abstract: Background: Anthracycline-induced cardiotoxicity is a serious complication in patients with malignant lymphoma (ML) who received chemotherapy, which threatens life prognosis and quality of life of patients. However, incidence and risk factors of cardiotoxicity in patients with ML who undergo intensive chemotherapy which aims complete remission is not clarified. Furthermore, prognosis after cardiotoxicity and that after recovery from cardiotoxicity have not been elucidated. Method: We screened 443 ML patients who received either rituximab (R)-CHOP or CHOP regimen between January 2008 and December 2017 at Nagoya City University Hospital. Two handled forty-four patients who underwent echocardiography before and after chemotherapy were enrolled and data were analyzed retrospectively. Cardiotoxicity was defined as a decline in left ventricular ejection fraction (LVEF) of 10% or greater and an LVEF was below 50%. Partial recovery was defined as a 5% or more of increase in LVEF and an LVEF was ≥50% after cardiotoxicity. Complete recovery was defined as an increase in LVEF became more than 95% of the baseline value. Patient's basic characteristics, chemotherapeutic regimen, laboratory data, echocardiographic data, and prognosis were collected from the medical records by two cardiologists and two hematologists. Result: At baseline, the median age was 71 years, the median cumulative dose of doxorubicin was 302 mg/m 2 and the median LVEF was 69%. During the follow-up period, cardiotoxicity was observed in 52 out of 244 patients (21%), 30 patients (12%) had a symptomatic heart failure, and 5 patients died from cardiovascular cause. Thirty-five patients developed cardiotoxicity during the first year of chemotherapy. Multivariate analysis identified that only the baseline LVEF (HR 0.949, 95% CI 0.919–0.981, p=0.002) was an independent risk factor for cardiotoxicity. In our study, patients who received more than 200 mg/m 2 of doxorubicin developed cardiotoxicity frequently. Among 52 patients who experienced cardiotoxicity, partial recovery and full recovery were observed in 18 (35%) and 4 (8%) patients, respectively. Four patients without recovery died due to heart failure and 1 patient with partial recovery died suddenly. Six out of 18 patients with partial recovery developed re-cardiotoxicity. Conclusion: ML patients who undergo more than 200 mg/m 2 of doxorubicin need a watchful follow-up. Only a baseline LVEF was an independent risk factor for cardiotoxicity. one third of patients with partial recovery developed re-cardiotoxicity. Funding Acknowledgement: Type of funding source: None